Analisis Keluhan Non-Auditory pada Pekerja Bagian Operasi yang Terpajan Kebisingan di Unit 5-7 Perusahaan Pembangkit Listrik PT X Tahun 2022 - Putri, Aisyah Raini Azzahra; Tejamaya, Mila (UI Scholars Hub, 2023)
Noise is unwanted sound that comes from objects or equipment from the production process that can cause health problems in the form of hearing loss and non-hearing complaints. Non-auditory effects are symptoms caused by exposure to noise, but not on the hearing organ. This effects that affect health and well- being in a person such as physiological effects, psychological effects, and communication disturbance. The purpose of this study was to determine the effect of the level of noise exposure, worker characteristics, and worker behavior on non-auditory among workers in the unit 5-7 area of power generation company PT. X on 2022. This research was conducted in March – May involving 58 workers who are operating division workers in units 5-7 area. The design used in this research is cross sectional and data collection is done by distributing questionnaires related to non-auditory. The independent variables in this study included noise intensity based on SEG, age, working period, use of Hearing Protection Devices (HPD), noise exposure outside of work activities, and training related to noise hazards. Based on research conducted on 58 operations workers, there is a relationship between noise intensity based on SEG and psychological complaints and communication complaints.